The activities of the International Labour Organization in the context of achieving the sustainable development goals - Yurii Dreval; Svitlana Zaika; Rastislav Tešovič; Martin Patoprstý (Entrepreneurship and Sustainability Issues)
This study examines the pivotal role of the International Labour Organization (ILO) in advancing the United Nations Sustainable Development Goals (SDGs), with a particular focus on promoting decent work and ensuring safe and secure working conditions. The article explores the mechanisms of international regulation of social and labour relations, highlighting both the historical and contemporary contributions of the ILO to global labour standards. It evaluates the transformative impact of the COVID-19 pandemic on progress toward achieving these goals, emphasising the emergent challenges and the need for innovative measures to enhance occupational safety and health. The study also analyses the ILO's historical legacy, which has shaped the international labour landscape over the past century, and discusses its current initiatives to address modern labour challenges. Special attention is given to the interconnection between economic growth, financial sustainability, and the implementation of international labour standards. By exploring specific strategies for improving workplace conditions and fostering financial resilience, the research presents actionable recommendations for global policymakers, organisations, and stakeholders. The findings underscore the importance of adopting a multidimensional and cooperative approach to resolving global social and labour issues. The study concludes that achieving the SDGs - particularly Goal 8 (Decent Work and Economic Growth) - requires strengthened international collaboration and a shared commitment to aligning labour policies with sustainable development objectives. This comprehensive examination of the ILO's role provides valuable insights into its strategic importance in ensuring equitable and sustainable progress in labour relations worldwide.